BAHAN AJAR KALKULUS 2 MENGGUNAKAN MACROMEDIA FLASH DAN MAPLE DI STKIP PGRI LUBUKLINGGAU - Retni Paradesa; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Jurnal Pendidikan Matematika, 2010)
This research purposes to result calculus II instructional material using valid, practical, and has potential effect Macromedia Flash and Maple toward studentâ€™s learning result. Valid can be described from the validity assessment result based on content (in accordance with calculus II subject) and construct (in accordance with media producing rule. It is practically described from the small group test result. Data collecting was carried out by document analysis and test. It was development research consist of three stages, i.e. analysis, design, and evaluation stage. The subject of the research was 28 second semester students in mathematics education program in STKIP PGRI Lubuklinggau. From the test teaching material potential effect towards the result can be gained 81.2 average welled categories.Â  Finally it can be concluded the effective developed teaching material in mathematic learning. Key Word: development research, calculus II